2020
DOI: 10.1111/1754-9485.13036
|View full text |Cite
|
Sign up to set email alerts
|

Particle therapy toxicity outcomes: A systematic review

Abstract: Owing to its physical properties, particle therapy (PT), including proton beam therapy (PBT) and carbon ion therapy (CIT), can enhance the therapeutic ratio in radiation therapy. The major factor driving PT implementation is the reduction in exit and integral dose compared to photon plans, which is expected to translate to reduced toxicity and improved quality of life. This study extends the findings from a recent systematic review by the current authors which concentrated on tumour outcomes for PT, to now exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 68 publications
(179 reference statements)
0
26
0
Order By: Relevance
“…A recent systematic review of 136 studies of both proton and carbon ion therapies (two thirds related to PBT alone) showed PBT provided at least equivalent tumour outcomes to conventional photon therapy. 1,2 There was the suggestion of reduced treatment morbidity associated with PBT for a range of tumour sites. 1,2 There are currently numerous trials underway comparing PBT and conventional photon beam RT in the treatment of several adult malignancies, including (but not limited to) breast, prostate, lung, head and neck, oesophagus and liver cancers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent systematic review of 136 studies of both proton and carbon ion therapies (two thirds related to PBT alone) showed PBT provided at least equivalent tumour outcomes to conventional photon therapy. 1,2 There was the suggestion of reduced treatment morbidity associated with PBT for a range of tumour sites. 1,2 There are currently numerous trials underway comparing PBT and conventional photon beam RT in the treatment of several adult malignancies, including (but not limited to) breast, prostate, lung, head and neck, oesophagus and liver cancers.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There was the suggestion of reduced treatment morbidity associated with PBT for a range of tumour sites. 1,2 There are currently numerous trials underway comparing PBT and conventional photon beam RT in the treatment of several adult malignancies, including (but not limited to) breast, prostate, lung, head and neck, oesophagus and liver cancers. 13,17 Numerous paediatric oncology clinical protocols allow for PBT, and registries have been established to capture prospective clinical and dosimetric data in patients treated with PBT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations